Symbolic Interactionism and Ethno-communicativeness of Select Libation Performances in Itu, South-South, Nigeria - Effiong, Kingsley James; Obong, Ubong Andem (International Journal of Education, Culture, and Society, 2024)
By highlighting the reverence for ancestors and the dependency of man on supernatural powers for his life, development, and well-being, libation performances reinforce ties between living things and ancestors as essential elements of African traditional culture and spirituality. However, due to the Itu people's attitude toward libation performances, the language of elements of libation performances including chants, prayers, invocations, incantation, and appeasement is disappearing. Therefore, the symbolic interaction in libation performance in Itu, South-South, Nigeria was explored in this study. Every item used, gesture made, song or prayer said, every unit of space and time that by tradition stands for something other than itself were analyzed. The study used the focused group interview (FGI), non-participant observation, and the survey method to collect information from 70 informants who were selected from the five (5) clans in the Itu Local Government Area. The EUDICO Linguistic Annotator (ELAN) was used to annotate, transcribe, and document the data while it was being descriptively analyzed. The study, among other things, indicated that ancestors may be addressed verbally or non-verbally over the course of the libation performance among the Itu people of Ibibio. Water, eggs, domestic animals, gin, clay, and other things are symbols. This study, among others, offers information on drinking that might supplement already available knowledge. It also aims to highlight the significance of the social values linked with drinking among the populace.